Outbreak of Serratia marcescens Coproducing ArmA and CTX-M-15 Mediated High Levels of Resistance to Aminoglycoside and Extended-Spectrum Beta-Lactamases, Algeria - Batah, R; Loucif, L; Olaitan, A.O. (My University, 2015)
Serratia marcescens is one of the most important pathogens responsible for nosocomial infections worldwide. Here, we have investigated the molecular support of antibiotic resistance and genetic relationships in a series of 54 S. marcescens clinical isolates collected from Eastern Algeria between December 2011 and July 2013. The 54 isolates were identified by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS). Antibiotic susceptibility testing was performed by disc diffusion and E-test methods. Antibiotic resistance genes were detected by polymerase chain reaction (PCR). The genetic transfer of antibiotic resistance was performed by conjugation using azide-resistant Escherichia coli J53 as the recipient strain, and plasmid analysis was done by PCR-based replicon typing. The relatedness of our isolates was determined by phylogenetic analysis based on partial sequences of four protein-encoding genes (gyrB, rpoB, infB, and atpD) and then compared to MALDI-TOF MS clustering. Thirty-five out of 54 isolates yielded an extended-spectrum b-lactamase (ESBL) phenotype and carried blaCTX–M-15 (n = 32), blaTEM-1 (n = 26), blaTEM-71 (n = 1), blaSHV-1a (n = 1), and blaPER-2 (n = 12). Among these isolates, we identified a cluster of 15 isolates from a urology unit that coharbored ESBL and the 16S rRNA methyltransferase armA. Conjugation was successful for five selected strains, demonstrating the transferability of a conjugative plasmid of incompatibility group incL/M type. Phylogenetic analysis along with MALDI-TOF clustering likely suggested an outbreak of such isolates in the urology unit. In this study, we report for the first time the co-occurrence of armA methyltransferase with ESBL in S. marcescens clinical isolates in Eastern Algeria.